2009
DOI: 10.1073/pnas.0905965106
|View full text |Cite
|
Sign up to set email alerts
|

Msh2-dependent DNA repair mitigates a unique susceptibility of B cell progenitors to c-Myc -induced lymphomas

Abstract: C-Myc is one of the most common targets of genetic alterations in human cancers. Although overexpression of c-Myc in the B cell compartment predisposes to lymphomas, secondary mutations are required for disease manifestation. In this article, we show that genetic deficiencies causing arrested B cell development and accumulation of B cell progenitors lead to accelerated lymphomagenesis in E c-myc transgenic mice. This result suggests that B cell progenitors are more prone than their mature counterparts to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
(59 reference statements)
3
16
1
Order By: Relevance
“…18 However, the same author later showed that Tcra 2/2 and Tcrd 2/2 -deficient Em-myc mice showed no significant impact on lymphomagenesis in Em-myc mice. 33 A possible explanation for the discrepancy with our data is that Figure 1C. Graphs represent the combined data from 2 independent experiments.…”
Section: Discussioncontrasting
confidence: 53%
“…18 However, the same author later showed that Tcra 2/2 and Tcrd 2/2 -deficient Em-myc mice showed no significant impact on lymphomagenesis in Em-myc mice. 33 A possible explanation for the discrepancy with our data is that Figure 1C. Graphs represent the combined data from 2 independent experiments.…”
Section: Discussioncontrasting
confidence: 53%
“…Taken together, the results presented by Reiss and colleagues provide novel evidence that MMR plays a critical role in preventing genetic events that lead to cellular transformation at very early stages, either during T cell development or at earlier stages of hematopoietic development. These data support a recent report that showed that Msh2 plays a critical tumor suppressive role in early B cell precursors [10]. The question of why the deletion of Mlh1 in thymocytes leads to precursor T cell lymphomas while deletion of Mlh1 in all tissues leads to precursor and mature T cell lymphomas will likely be the subject of further investigation.…”
supporting
confidence: 70%
“…59,85,86 By spectral karyotype, the B-cell lineage tumors of MSH6-deficient mice did not bear chromosomal translocations, although chromosomal aneuploidies were common. Similar abnormalities have been observed in embryonic fibroblasts from mice deficient in MSH2 82,87 and in colon cancers in MMR-deficient mice and humans with microsatellite instability. 61,62 Array comparative genomic hybridization, with its greater resolution, did reveal chromosomal regions that were amplified or deleted, and some of these were common to two or three of the four tumors examined (Table 3).…”
Section: Msh6supporting
confidence: 58%
“…46 Likewise the recently reported ability of MSH2 to suppress E-myc-driven Bcell lymphomas seems to be unrelated to MMR-dependent apoptosis. 82 On the other hand, the unique genotoxic stress to which GC B cells are subjected 18 and the intrinsic MSI exhibited by these cells 83 raise the possibility that MSH6 protects B cells through its traditional enzymatic role in mismatch repair.…”
Section: Msh6mentioning
confidence: 99%